Epidemiologic threats and outcome of evolving COVID-19-associated mucormycosis from a referral hospital in Egypt - Safaa Elserougy; Muhammad Abdel-Ghaffar; Eman Medhat; Ahmed Heiba; Weam Shaheen; Elham Mostafa; Hala Mahfouz; Samah Abdel-Hafez; Mohammad S Mahfouz; Shimaa Afify; Omnia Ali; Enass El-Sayed; et al. (Journal of Infection in Developing Countries)
Introduction: The present study aimed to explore the epidemiologic threats and factors associated with the coronavirus disease 2019 (COVID-19)-associated mucormycosis (CAM) epidemic that emerged in Egypt during the second COVID-19 wave. The study also aimed to explore the diagnostic features and the role of surgical interventions of CAM on the outcome of the disease in a central referral hospital.